ELABORATION OF TASLIYAH VERSES: A HERMENEUTIC STUDY ON 'HĀSHIYAH AS-SĀWI ‘ALĀ TAFSĪR AL-JALĀLAIN - Mujtaba, Aqil; Bakar, Abu (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The concept of ‘tasliyah’ in the Qur’an which means consolation or reassurance plays a significant role in Tafseer and has been extensively discussed by Islamic scholars. One of the important commentaries of the Qur’an examining this concept is 'Hāshiyah as-Sāwi 'alā Tafsīr al-Jalālain' by Ahmad al-Ṣāwī, an influential figure in Islamic education in Indonesia. This study aims to analyze the interpretation of tasliyah verses in the commentary and to find out how hermeneutics helps explain Ahmad al-Ṣāwī’s approach. This research uses a qualitative approach which includes hermeneutics, linguistic, Maqasid Tafseer, and socio-historical analysis approaches, with Krippendorff content-analysis as the method to analyze the data. The results of this study show that the Tafseer on tasliyah verses by integrating linguistic, literary, and Sufism aspects not only were interpreted as comfort in distress but also as strengthening faith and resilience. Through hermeneutics, the interpretation explores historical, social, and psychological contexts influencing al-Saawi’s reasoning, which offers a broader and deeper understanding of the tasliyah concept in Islamic spiritual and psychological contexts. This study highlights the importance of contexts in understanding consolation messages and spiritual reassurance addressed to the Prophet Muhammad as well as provides an insight into how social cognition plays a crucial role in interpreting religious texts.